Ta’lim Al-Lughah Al ‘Arabiyyah fi ‘Asr Al-Thabiiy Al-Jadid fi Dhau’ Al-Ta’lim Al-Mudmaj - Puji Rahayu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The learning process cannot be separated from the presence of the teacher. The role of the teacher in the learning process is the very dominant decisive factor in education in general, because the teacher plays a role in the learning process, where the learning process is the core of the educational process. During this pandemic, learning cannot take place face to face. In order to conduct distance learning online and offline, the choice of learning methods is very important because it will have an impact on the smooth implementation of learning. One method that can be used is the